The Dynamics of Emotional Intelligence in The Sunnah: An Analytical Study of The Prophet’s (PBUH) Approach to Crisis Management (Contrarius Series: Law & Social Justice, 2026)
This research investigates Emotional Intelligence (EI) through the Prophetic methodology, focusing on its application in crisis management. Although EI is a modern psychological framework, its core pillars, specifically self-management and empathy are fundamentally rooted in the life of Prophet Muhammad (PBUH). This study employs a descriptive-analytical approach to examine how the Prophet (PBUH) utilized these emotional competencies to navigate complex social and personal challenges. The study provides specific evidence of the Prophet’s (PBUH) emotional mastery. For instance, his self-management is exemplified in the "Year of Sorrow," where he maintained psychological resilience despite immense personal loss. Furthermore, his empathy is demonstrated in the "Conquest of Makkah," where he prioritized emotional reconciliation over retribution. These examples move beyond generalities, illustrating a sophisticated model of emotional leadership. A key focus of this research is the relevance of the Prophetic model to contemporary challenges. In an era marked by escalating psychological crises and social fragmentation, the Prophet’s (PBUH) approach offers a practical framework for conflict resolution and social cohesion. The findings suggest that integrating these spiritual-emotional strategies can significantly enhance modern interpersonal relationships. The study concludes that the Prophet (PBUH) serves as a timeless archetype for emotional intelligence, providing balanced solutions for managing the complexities of the modern world with wisdom and compassion.